MANAGERIAL OWNERSHIP AS A MODERATION OF THE RELATIONSHIP BETWEEN RETURN ON ASSETS (ROA) AND PRICE BOOK VALUE (PBV) - Mulyani, Ana Susi (Management Science Research Journal, 2023)
The aim of this research is to determine institutional ownership as a moderator of the relationship between return on assets (ROA) and price book value (PBV). The population in this research is all automotive and component sector companies listed on the Indonesia Stock Exchange for the period 2018 - 2021. The sample selected in this research using the purposive sampling method was 13 companies. The analytical method used is descriptive analysis research. The data analysis technique used is Moderating Regression Analysis (MRA). The research results show that: (1) Return On Assets (ROA) has a positive and significant effect on Price Book Value, (2) Institutional Ownership is unable to moderate the relationship between Return On Assets (ROA) and Price Book Value (PBV).